Impact of Compression Stockings vs. Continuous Positive Airway Pressure on Overnight Fluid Shift and Obstructive Sleep Apnea among Patients on Hemodialysis - Silva, Bruno C.; Santos, Roberto S. S.; Drager, Luciano F.; Coelho, Fernando M.; Elias, Rosilene M. (Frontiers in Medicine, 2017)
Introduction: Obstructive Sleep Apnea (OSA) is common in edematous states, notably in hemodialysis patients. In this population, overnight fluid shift can play an important role on the pathogenesis of OSA. The effect of compression stockings (CS) and continuous positive airway pressure (CPAP) on fluid shift is barely known. We compared the effects of CS and CPAP on fluid dynamics in a sample of patients with OSA in hemodialysis, through a randomized crossover study. Methods: Each participant performed polysomnography (PSG) at baseline, during CPAP titration and after one week of wearing CS. Neck circumference (NC) and segmental bioelectrical impedance were done before and after PSG. Results: Fourteen patients were studied (53±9 years; 57% men; body mass index 29.7±6.8 kg/m²). AHI decreased from 20.8 (14.2;39.6) at baseline to 7.9 (2.8;25.4) during CPAP titration and to 16.7 (3.5;28.9) events/hour after wearing CS (CPAP vs. baseline, p=0.004; CS vs. baseline, p=0.017; and CPAP vs. CS, p=0.017). Nocturnal intracellular trunk water was higher during CS when comparing baseline, CPAP and CS (p=0.03). CS reduced the fluid accumulated in lower limbs during the day, although not significantly. Overnight fluid shift at baseline, CPAP and CS was -183±72, -343±220, and -290±213ml, respectively (p=0.006). Overnight NC increased at baseline (0.7±0.4cm), decreased after CPAP (-1.0±0.4cm), and while wearing CS (-0.4±0.8cm) (CPAP vs. baseline, p<0.0001; CS vs. baseline, p=0.001; CPAP vs. CS, p=0.01). Conclusions: CS reduced AHI by avoiding fluid retention in the legs, favoring accumulation of water in the intracellular component of the trunk, thus avoiding fluid shift to reach the neck. CPAP improved OSA by exerting local pressure on upper airway, with no impact on fluid redistribution. CPAP performed significantly better than CS both for reduction of AHI and overnight reduction of NC. Complementary studies are needed to elucidate the mechanisms by which CPAP and CS reduce NC.